-7=-3+f

Simple and best practice solution for -7=-3+f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7=-3+f equation:



-7=-3+f
We move all terms to the left:
-7-(-3+f)=0
We add all the numbers together, and all the variables
-(f-3)-7=0
We get rid of parentheses
-f+3-7=0
We add all the numbers together, and all the variables
-1f-4=0
We move all terms containing f to the left, all other terms to the right
-f=4
f=4/-1
f=-4

See similar equations:

| 8x^2-2=24 | | 3v-2v-v+v=14 | | 1/3(6-9x)=6x+11 | | 31=3(x-3)-8x | | 15k-5k-6k=12 | | 4(p–7)= | | 4y-7=-2y+11 | | 15k−5k−6k=12 | | 15j-9j-j+j-3j=18 | | 5x-13=7x+8 | | x^2-11.25x=1/45 | | –6+2k=k | | 6r+3=4r+11 | | −14=x−12 | | .65x=500 | | –9+5m=8m | | (x/2)+(1/2)=44 | | x+3.17=12.08 | | 5+3x+1x=21 | | q+6=-12 | | 0.05(4x)=16.2 | | r2+14r=39 | | 85+5x=20 | | -8(t-100)=8 | | 23-3x=40 | | -3(6x-2)+5=-18x+11 | | 22+6z=88 | | n/6+65=72 | | 7x-11=2x=4 | | x^2-235+10500=0 | | v-7.83=9.6 | | 2v+9=46 |

Equations solver categories